Cover Feature: Controlling Size‐Dispersion of Single Walled Carbon Nanotubes by Interaction with Polyoxometalates Armed with a Tryptophan Tweezer (Eur. J. Inorg. Chem. 3‐4/2019). Issue 3 (22nd January 2019) - Syrgiannis, Zois; Trautwein, Guido; Calvaresi, Matteo; Modugno, Gloria; Zerbetto, Francesco; Carraro, Mauro; Prato, Maurizio; Bonchio, Marcella
Abstract : The Cover Feature shows how tryptophan tweezers, anchored on a polyoxometalate (POM) scaffold, intercalate into single‐walled carbon nanotube (SWCNT) bundles, leading to a selective dispersion and enrichment of nanotubes with a small diameter range. The engineering of the POM tweezer and of its supramolecular surface interactions can be used to evaluate the impact of the amino acid terminals on the recognition of pristine SWCNTs. This information can address possible SWCNT/peptide interactions and their impact on the cellular level for drug delivery and CNS‐based therapy. This work opens new possibilities for the fabrication of nanohybrid functional interfaces. More information can be found in theCommunication by M. Calvaresi, M. Prato, M. Bonchio et al.